Meat Consumption, Heterocyclic Amines, and Colorectal Cancer Risk: The Multiethnic Cohort Study - Ollberding, Nicholas J. (2012)
Greater consumption of red and processed meat has been associated with an increased risk of colorectal cancer in several recent meta-analyses. Heterocyclic amines (HCAs) have been hypothesized to underlie this association. In this prospective analysis conducted within the Multiethnic Cohort Study, we examined whether greater consumption of total, red, or processed meat was associated with the risk of colorectal cancer among 165,717 participants who completed a detailed food frequency questionnaire at baseline. In addition, we examined whether greater estimated intake of HCAs was associated with the risk of colorectal cancer among 131,763 participants who completed a follow-up questionnaire that included a meat-cooking module. A total of 3,404 and 1,757 invasive colorectal cancers were identified from baseline to the end of follow-up, and from the date of administration of the meat-cooking module to the end of follow-up, respectively. Proportional hazards models were used to estimate basic and multivariable-adjusted relative risks (RRs) and 95% confidence intervals (CIs) for colorectal cancer associated with dietary exposures. In multivariable models, no association with the risk of colorectal cancer was detected for density-adjusted total meat (RR(Q5 vs Q1)=0.93 [0.83–1.05]), red meat (RR =1.02 [0.91–1.16]), or processed meat intake (RR =1.06 [0.94–1.19]), or for total (RR =0.90 [0.76–1.05]) or specific HCA intake whether comparing quintiles of dietary exposure or using continuous variables. Although our results do not support a role for meat or for HCAs from meat in the etiology of colorectal cancer, we cannot rule out the possibility of a modest effect.